Birch pollen‐specific subcutaneous immunotherapy reduces ILC2 frequency but does not suppress IL‐33 in mice. Issue 11 (12th September 2018) - van Rijt, Leonie S.; Logiantara, Adrian; Canbaz, Derya; van Ree, Ronald
Abstract: Background: The underlying mechanism of allergen‐specific subcutaneous immunotherapy (SCIT) is not yet fully understood, but suppression of allergen‐specific Th2 cells and production of allergen‐specific IgG4 antibodies are two hallmarks. The impact on the innate arm of the immune system is far less clear. Objective: The aim of this study was to investigate the effect of birch pollen (BP) SCIT on the innate immune response in a BP SCIT mouse model. Methods: Mice with birch pollen‐induced allergic airway inflammation received weekly subcutaneous immunotherapy injections with birch pollen extract (BPE) adsorbed to alum. The effect of the BP SCIT on innate cytokine levels in lung, the number and the functionality of ILC2s and the airway inflammation was determined. Results: Mice with BP allergy had an increased level of the innate cytokines IL‐33, IL‐25, GM‐CSF and IL‐5 + ILC2s in the lungs. BP SCIT suppressed the number of IL‐5 + ILC2s, mast cell tryptase release, Th2 cytokine production, eosinophil recruitment and peribronchial inflammatory infiltrates. In contrast, innate cytokine production and collagen deposition in the airways were not affected. Conclusion and Clinical Relevance: BP SCIT is able to suppress the adaptive and part of the innate immune response, but this is not sufficient to inhibit collagen deposition and the IL‐33 expression in the airways in mice.